Inactivation of Avian Influenza Viruses on Porous and Non‐porous Surfaces is Enhanced by Elevating Absolute Humidity. Issue 4 (5th April 2016) - Guan, J.; Chan, M.; VanderZaag, A.
Summary: This study was to evaluate the effect of absolute humidity (AH), a combined factor of temperature and relative humidity (RH), on inactivation of avian influenza viruses (AIVs) on surfaces. Suspensions of the H9N2 or H6N2 AIV were deposited onto carrier surfaces that were either porous (pine wood) or non‐porous (stainless steel, synthetic rubber and glass). The inoculated carriers were incubated at 23, 35 or 45°C with 25% or 55% RH for up to 28 days. After incubation, virus was recovered and quantified by chicken embryo assays. The time required to obtain a log10 reduction in virus infectivity (D‐value) was estimated using a linear regression model. At AH of 5.2 g/m 3 (23°C & 25% RH), both viruses survived up to 14 days on the porous surface and for at least 28 days on the non‐porous surfaces. The corresponding D‐values for H9N2 and H6N2 were 1.49 and 6.90 days on the porous surface and 7.81 and 12.5 days on the non‐porous surfaces, respectively. In comparison, at AH of 9.9 g/m 3 (35°C & 25% RH) or 11.3 g/m 3 (23°C & 55% RH), the D‐values for H9N2 and H6N2 dropped to ≤0.76 day on the porous surface and to ≤1.81 days on the non‐porous surfaces. As the AH continued to rise from 11.3 to 36.0 g/m 3, the D‐value for both viruses decreased further. The relationship between D‐value and AH followed a form of y  =  ax − b for both viruses. The D‐values for H9N2 virus were significantly lower ( P  < 0.05) than those for H6N2 virus. Exposure to ammonia gas at concentrations of 86 and 173 ppm did not significantly alter test results. The findings give evidence that increasing the AH in poultry buildings following an outbreak of disease could greatly reduce the length of time required for their decontamination.